LEGAL DUALISM CONCERNING AGRARIAN CONFLICT OF LAND IN BONGKORAN, WONGSOREJO, REGENCY OF BANYUWANGI - Sholahudin, Umar (Jurnal Analisa Sosiologi, 2023)
This study aims to analyze the practice of legal dualism in agrarian conflicts of the Bongkoran land, Wongsorejo, Banyuwangi Regency. Agrarian conflicts are structural conflicts, one of which originates from legal conflicts; state law and people's law. There are different legal bases used by state/government, corporation, and society. Government and companies rely more on the legal-formal (de jure) aspect, that land ownership and control rights are based on formal laws and procedures, that is proof of concession permit (HGU or HGB). Meanwhile, the community relies more on the socio-historical aspect, that the community has lived in, controlled, and used the land communally and for generations (de facto). This research focuses on how the practice of legal dualism in agrarian conflicts in the land of Bongkoran Wongsorejo. This study uses a legal sociology approach with a participatory method. The results showed; Legal dualism in agrarian conflicts has contrasting characteristics and characters that are difficult to be compromised and resolved fairly. The strong domination and hegemony of state law over the people's law, making the conflict more sharpened, people's rights over land increasingly seized, and often lead to acts of violence. There needs to be equal dialogue and communication between the (law) of the state and the (law) of the people in an intense and deliberative manner to produce a more just consensus (legal product). Settlement of agrarian conflicts is not enough to use legalistic-positivistic state legal instruments, but it is need to pay attention to community law that has local wisdom and is more oriented towards justice aspect Key Words : Legal Dualism, Agrarian Conflict, Bongkoran Land, Banyuwangi Regency AbstrakPenelitian ini bertujuan untuk menganalisis praktik dualisme hukum dalam konflik agraria di tanah Bongkoran, Wongsorejo, Kabupaten Banyuwangi. Konflik agraria merupakan konflik struktural yang salah satunya bersumber dari konflik hukum; hukum negara dan hukum rakyat. Dasar hukum yang digunakan oleh negara/pemerintah, korporasi, dan masyarakat berbeda-beda. Pemerintah dan perusahaan lebih mengandalkan aspek legal-formal (de jure), bahwa hak penguasaan dan penguasaan tanah didasarkan pada hukum dan prosedur formal, yaitu bukti izin pengusahaan (HGU atau HGB). Sedangkan masyarakat lebih mengandalkan aspek sosio-historis, bahwa masyarakat telah mendiami, menguasai, dan menggunakan tanah secara komunal dan turun-temurun (de facto). Penelitian ini berfokus pada bagaimana praktik dualisme hukum dalam konflik agraria di tanah Bongkoran Wongsorejo. Penelitian ini menggunakan pendekatan sosiologi hukum dengan metode partisipatif. Hasilnya menunjukkan; Dualisme hukum dalam konflik agraria memiliki sifat dan karakter yang bertolak belakang sehingga sulit untuk dikompromikan dan diselesaikan secara adil. Kuatnya dominasi dan hegemoni hukum negara atas hukum rakyat, membuat konflik semakin menajam, hak rakyat atas tanah semakin direbut, dan tak jarang berujung pada tindakan kekerasan. Perlu adanya dialog dan komunikasi yang setara antara (hukum) negara dan (hukum) rakyat secara intens dan musyawarah untuk menghasilkan konsensus (produk hukum) yang lebih berkeadilan. Penyelesaian konflik agraria tidak cukup menggunakan instrumen hukum negara legalistik-positivistik, tetapi perlu memperhatikan hukum masyarakat yang memiliki kearifan lokal dan lebih berorientasi pada aspek keadilan. Kata Kunci : Dualisme Hukum, Konflik Agraria, Tanah Bongkoran, Kabupaten Banyuwangi.